Heterogeneous Catalytic Hydrogenation of Biobased Levulinic and Succinic Acids in Aqueous Solutions. Issue 12 (23rd August 2013) - Corbel‐Demailly, Louis; Ly, Bao‐Khanh; Minh, Doan‐Pham; Tapin, Benoit; Especel, Catherine; Epron, Florence; Cabiac, Amandine; Guillon, Emmanuelle; Besson, Michèle; Pinel, Catherine
Abstract Supported noble‐metal catalysts (Ru, Pd or Pt) and the corresponding Re‐promoted catalysts exhibit a high activity for the hydrogenation of biobased carboxylic acids. Levulinic acid and succinic acid are converted into the lactones or the diols depending on the nature of the catalyst and the reaction conditions. The highest selectivity to 1, 4‐pentanediol of 82 % is achieved at 140 °C in the presence of the 1.9 % Ru–3.6 % Re/C catalyst.